Escorpiones (Arachnida) del Archipiélago de Bocas del Toro, Panamá - Montoya, Michel; de Armas, Luis F (Revista de Biología Tropical, 2002)
Four species of buthid scorpions (Ananteris platnicki Lourenço, 1993; Centruroides limbatus [Pocock, 1898]; Tityus pachyurus [Pocock, 1897]; and T. ocelote Francke and Stockwell, 1987) are recorded for the first time from some islands and cays of the Bocas del Toro Archipelago, Panama. Morphological variation and ecological data are given for all the species. This is the first Panamanian record for both C. limbatus and T. ocelote. The scorpion fauna of the Bocas de Toro Archipelago is related with the recent fauna of the Atlantic continental lowland region of Costa Rica and Panama and includes Amazonian-Guyanese (genera Ananteris and Tityus) as well as Mexican-North Central American (genus Centruroides) elements